Allogeneic Skin Substitutes Versus Human Placental Membrane Products in the Management of Diabetic Foot Ulcers: A Narrative Comparative Evaluation of the Literature. (March 2019) - Luck, Joshua; Rodi, Timo; Geierlehner, Alexander; Mosahebi, Afshin
Outcomes following standard wound care (SWC) for diabetic foot ulcers (DFUs) remain suboptimal. Supplementing SWC with tissue engineered allogeneic cellular wound therapies represents an emerging treatment strategy. This review aimed to evaluate the efficacy and safety of allogeneic skin substitutes and human placental membrane allografts in the management of DFUs. Ovid MEDLINE and Embase databases were searched from inception to October 2017. Any randomized controlled trial (RCT) with an allogeneic skin substitute or placental membrane allograft intervention group was included. Our primary outcome measure was the proportion of completely healed ulcers. Secondary outcome measures included time to complete wound healing and local adverse event rates. Each study was assessed for risk of bias and the quality of evidence was appraised using the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) approach. Moderate quality evidence from 11 included RCTs demonstrated that both allogeneic cellular approaches improve the proportion of completely healed ulcers at 6 and 12 weeks. One RCT showed that a placental membrane allograft was superior to an allogeneic skin substitute, although this has yet to be repeated in other studies. The addition of allogeneic cellular wound products to SWC improves DFU outcomes. Further studies are required to conclusively establish if placental membrane allografts are superior to allogeneic skin substitutes.